2019
DOI: 10.3390/informatics6010008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Awareness and Perception of Botnet Activity within Consumer Internet-of-Things (IoT) Networks

Abstract: The growth of the Internet of Things (IoT), and demand for low-cost, easy-to-deploy devices, has led to the production of swathes of insecure Internet-connected devices. Many can be exploited and leveraged to perform large-scale attacks on the Internet, such as those seen by the Mirai botnet. This paper presents a cross-sectional study of how users value and perceive security and privacy in smart devices found within the IoT. It analyzes user requirements from IoT devices, and the importance placed upon securi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The results indicated that mirai botnet is more resilient and supports more effective attacks. An evaluation on how users perceive security and privacy in IoT devices with respect to botnet activities was conducted by McDermott et al [24]. The authors utilised experiments to examine users' ability to detect threats.…”
Section: A Rq1:what Are the Contributions Of The Primary Studies?mentioning
confidence: 99%
“…The results indicated that mirai botnet is more resilient and supports more effective attacks. An evaluation on how users perceive security and privacy in IoT devices with respect to botnet activities was conducted by McDermott et al [24]. The authors utilised experiments to examine users' ability to detect threats.…”
Section: A Rq1:what Are the Contributions Of The Primary Studies?mentioning
confidence: 99%
“…McDermott et al [8] demonstrate that users are aware of the challenges related to the security and privacy of devices within their home network, but the majority simply lack the skills, technology and knowledge necessary to identify potential vulnerabilities. This gap between user awareness and technical ability is an issue that should be addressed to provide the average consumer with the means to accurately monitor their own devices for security issues.…”
Section: Introductionmentioning
confidence: 99%
“…However, they might not necessarily have the security expertise and budget allocated to conduct security processes such as threat modelling, risk assessment and security audits. This can result in poor quality and insecure systems that could be relatively easily exploited by hackers due to several security vulnerabilities they may contain [17,18].…”
Section: Introductionmentioning
confidence: 99%